Dianogsis Anak Didik Dalam Kasus Kesulitan Belajar - Siti Nurlatifah; Nur Yanah (PROPHETIK Jurnal Kajian Keislaman, 2023)
Learning difficulties are conditions where students experience difficulty in learning. In the learning process, it is possible that there are students who experience difficulties in the learning process, in fact students who experience learning difficulties are often labeled stupid by those around them. At elementary school age, the cases of learning difficulties that are often encountered are in the ability to read, write and count. Students who experience learning difficulties will have an impact on low academic achievement. a location of learning difficulties faced by students and to find solutions. If students' learning difficulties are ignored, then the learning objectives will not be achieved properly. To overcome these difficulties, students need help, both in digesting teaching materials and in overcoming other obstacles. Students' learning difficulties must be identified and overcome as early as possible, so that instructional objectives can be achieved well. So it is necessary to carry out a diagnosis. The implementation of this diagnosis helps students to obtain optimal learning outcomes. It is hoped that the implications of this research can help teachers in providing action to overcome various learning difficulties experienced by students. Kesulitan belajar adalah kondisi dimana siswa mengalami kesulitan dalam belajar. Dalam proses pembelajaran tidak menutup kemungkinan adanya siswa yang mengalami kesulitan dalam proses pembelajaran, bahkan siswa yang mengalami kesulitan belajar sering dilabeli bodoh oleh orang yang berada disekitarnya. Pada usia sekolah dasar kasus kesulitan belajar yang sering ditemui adalah pada kemampuan membaca, menulis dan berhitung. Siswa yang mengalami kesulitan belajar akan berdampak pada prestasi akademik yang rendah. a letak kesulitan belajar yang di hadapi oleh siswa serta untuk mencari pemecahannya. Jika kesulitan belajar siswa tersebut dibiarkan, maka tujuan pembelajaran tidak akan tercapai dengan baik. Untuk mengatasi kesulitan tersebut, siswa memerlukan bantuan, baik dalam mencerna bahan pengajaran maupun dalam mengatasi hambatan-hambatan lain. Kesulitan belajar siswa harus dapat diketahui dan dapat diatasi sedini mungkin, sehingga tujuan instruksional dapat tercapai dengan baik. Maka perlu dilakukan diagnosis dari pelaksanaan diagnosis ini membantu siswa untuk memperoleh hasil belajar yang optimal. Implikasi penelitian ini diharapkan dapat membantu guru dalam memberikan tindakan untuk mengatasi berbagai kesulitan belajar yang dialami siswa.